PrOgnosis in Pulmonary Embolism (PoPE): 30-Day mortality risk score based on five admission parameters - Gerardo, Filipa (2024)
© 2023 Published by Elsevier Espa˜na, S.L.U. on behalf of Sociedade Portuguesa de Cardiologia. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).